Experimental investigation of flutter characteristics of shallow Π section at post-critical regime. (July 2019) - Tang, Y.; Hua, X.G.; Chen, Z.Q.; Zhou, Y.
Abstract: The aeroelastic response of a bridge deck at post-critical regime of flutter is featured by limit cycle oscillation (LCO) due to nonlinearities in both fluid and structural-dynamics. In this study, wind tunnel tests are conducted on an elastically-mounted rigid section model with shallow Π cross section, which is free to vibrate in vertical and torsional directions. The aim is to explore the response characteristics of shallow Π cross section at different initial angles of attack (AOA) for wind speeds above the flutter threshold. Firstly, the structural nonlinearities of the elastically-mounted system for section model are carefully characterized in still air to evaluate their effects on aeroelastic responses of the model. Then, post-critical responses of the model subjected to flutter instability are measured at different initial AOA. Experimental phenomena in terms of the aerostatic displacement, critical velocity, steady state amplitude, time history of oscillations, frequency characteristics, phase-angle shift between heaving and torsional motions, and damping evolution are discussed in detail as well as the influence of structural damping on post-critical responses. The results show that the oscillations of Π cross section at post-critical regime of flutter grow slowly with wind speed, instead of building up to large amplitude abruptly. Both the critical flutter velocity and the steady state amplitude of flutter oscillations are sensitive to initial AOA and structural damping. One degree of freedom (DOF) motion approximation is suitable for small amplitude flutter oscillations. For large amplitude oscillation description of coupled 2-DOF motion would be necessary for the bluff Π cross section. The torsional and vertical heaving oscillations tend to be synchronous at high velocity with large amplitude. Compared to slight nonlinear structural damping in the dynamic system, the nonlinear aerodynamic damping related to higher-order terms of displacement is more significant, implying that the aerodynamic nonlinearity is the main source leading to LCO.